PENGARUH KEPEMILIKAN MANAJERIAL, KOMITE AUDIT, DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Eva Noviana Hidayati, (2022)
This research aims to empirically examine the effect of managerial ownership, audit committee, and audit quality on integrity of financial statement. This research uses manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange during the period 2017-2020 as a sample. The sampling technique used in this research is purposive sampling with acquisition of sampling 133 samples. The method used in this study a quantitative research method using secondary data. The analytical technique used is data panel regression analysis using STATA v.14.2. The results show that (1) managerial ownership has a positive effect on the integrity of financial statements (2) the audit committee has no effect on the integrity of financial statements, and (3) audit quality has no effect on the integrity of financial statements.